The Effect of Workload, Work Environment, and Remuneration Policy on Employee Performance through Work Motivation at the Regional Development Planning, Research, and Development Agency - Prasetyowati, Chandra; Sundjoto; Rahayu, Sri; Fitrianty, Rifda (Asosiasi Ahli Administrasi Indonesia, 2025)
Public sector organizations face increasing challenges caused by expanding administrative duties, complex development planning, and growing public expectations for better services. These conditions place strong demands on employees, who must perform effectively despite pressures related to workload, workplace conditions, and compensation systems. This study aims to investigate how workload, work environment, and remuneration policies influence employee performance, with work motivation acting as a linking mechanism. The research used a quantitative approach by involving all employees in a regional development planning agency (BAPPELITBANGDA Pasuruan Regency), collecting data through structured questionnaires, and analyzing the relationships using a partial least squares technique. The findings reveal that balanced workloads, supportive work environments, and fair remuneration practices encourage higher motivation and lead to better employee performance. From a managerial perspective, the study highlights the importance of fair task distribution, improvement of physical and social work conditions, and the development of transparent, performance-based remuneration systems to maintain productivity and institutional effectiveness.